Review of the genus Ishiharella Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae), with description of two new species - Wang, Ran; Zhang, Yalin; Cao, Yanghui (Zootaxa, 2025)
The generic characteristics of Ishiharella Dworakowska are redefined based on two new species from southern China, I. trifurcata and I. wuxiensis spp. nov., and a new combination Ishiharella spinosa (Sohi & Mann, 1990) comb. nov. removed from Daluana. A key to males of all known species of Ishiharella from worldwide is also given. A detailed morphological description about differences between the new species and related species, illustrations of the male genitalia and habitus photos of the new species are provided.